YKL-40 as a possible marker of neutrophilic asthma - Specjalski, Krzysztof; Romantowski, Jan; Niedoszytko, Marek (Frontiers in Medicine, 2023)
Asthma is a heterogeneous chronic disorder of the airways, with inflammation and bronchial hyperresponsiveness as its major underlying phenomena. Asthmatics vary in terms of inflammation pattern, concomitant pathologies, and factors aggravating the course of the disease. As a result, there is a need for sensitive and specific biomarkers that could facilitate diagnosing asthma as well as phenotyping in everyday practice. Chitinases and chitinase-like proteins (CLPs) seem promising in this field. Chitinases are evolutionarily conserved hydrolases that degrade chitin. In contrast, CLPs bind chitin but do not have degrading activity. Mammalian chitinases and CLPs are produced by neutrophils, monocytes, and macrophages in response to parasitic or fungal infections. Recently, several questions have been raised about their role in chronic airway inflammation. Several studies demonstrated that overexpression of CLP YKL-40 was associated with asthma. Moreover, it correlated with exacerbation rate, therapy resistance, poor control of symptoms, and, inversely, with FEV1. YKL-40 facilitated allergen sensitization and IgE production. Its concentration was elevated in bronchoalveolar lavage fluid after an allergen challenge. It was also found to promote the proliferation of bronchial smooth muscle cells and correlate with subepithelial membrane thickness. Thus, it may be involved in bronchial remodeling. Associations between YKL-40 and particular asthma phenotypes remain unclear. Some studies showed that YKL-40 correlates with blood eosinophilia and FeNO, suggesting a role in T2-high inflammation. Quite the opposite, cluster analyses revealed the highest upregulation in severe neutrophilic asthma and obesity-associated asthma. The main limitation in the practical application of YKL-40 as a biomarker is its low specificity. High serum levels of YKL-40 were also found in COPD and several malignancies, in addition to infectious and autoimmune diseases. To conclude, the level of YKL-40 correlates with asthma and some clinical features in the whole asthmatic population. The highest levels are found in neutrophilic and obesity-related phenotypes. However, due to its low specificity, the practical application of YKL-40 remains uncertain but could be useful in phenotyping, especially when combined with other biomarkers.